Peran Guru dalam Penguatan Profil Pelajar Pancasila Siswa Kelas II di SDN Gunggung - Nur Ilham Mubarak; Anang Hadi Cahyono; ACH. Puniman (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
The purpose of this study is to explain how the role of teachers in strengthening the profile of Pancasila students is applied by highlighting how the role played by teachers in implementing it. In addition, this study intends to describe the challenges and solutions in implementing the Pancasila student profile. This study uses a qualitative method and a case study approach. This study was conducted at SDN Gunggung with the principal, class teachers, and students as data sources. Data sources use primary and secondary data sources and data collection uses observation, interviews, and documentation. The data analysis technique for this study uses data reduction, data presentation, and drawing conclusions. The data is checked for validity using source triangulation, technique triangulation and time triangulation. From the results of this study, it can be concluded that the role of teachers in strengthening the profile of class II students at SDN Gunggung is namely teachers as mentors, teachers as facilitators and teachers as evaluators.